Seasonal Tourism in Pangururan District, Samosir Regency, Indonesia (International Journal of Architecture and Urbanism, 2021)
Abstract. Indonesia has a variety of tribes and cultures that cannot be separated from the natural beauty which is a tourist destination for the beauty of Lake Toba in North Sumatra. Pangururan District, Samosir Regency is one of the priority points of tourists because Pangururan District is the capital of Samosir Regency so that the impact of the influence of tourist destinations becomes a strategic area for national and international tourism. A person's fatigue in carrying out daily activities makes travelling one of the solutions to calm the mind after facing someone's busy life. Tourism has categories according to conditions, one of which is tourism. Tourism is defined as a form of sustainable tourist visits, in terms of attracting local and non-local tourists with the condition of a tourist destination provided with the natural beauty of Pangururan District, Samosir Regency. Tourism that occurs with tourist visits based on the holiday season and weekdays on tourist visits has increased during holidays with a high number compared to normal days. Tourism management still provides the best service so that tourists don't just drink. In this case, tourism shows the condition of tourists who visit during the holiday season so that they get a response so that the improvement of tourism management is better, this is evidenced by showing the results of field observations. With regard to tourism, it shows that the results are processed based on the opinion of the community as both visitors and local people